2022
DOI: 10.3390/cancers14246115
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cell-Free DNA in Cancer Treatment Decision Making

Abstract: The aim of this review is to evaluate the present status of the use of cell-free DNA and its fraction of circulating tumor DNA (ctDNA) because this year July 2022, an ESMO guideline was published regarding the application of ctDNA in patient care. This review is for clinical oncologists to explain the concept, the terms used, the pros and cons of ctDNA; thus, the technical aspects of the different platforms are not reviewed in detail, but we try to help in navigating the current knowledge in liquid biopsy. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 266 publications
0
6
0
Order By: Relevance
“…The rise of ccfDNA has been buoyed by advancements in genomic technologies, enabling the detection and analysis of these DNA fragments with unprecedented precision and sensitivity. Its emergence as a diagnostic tool is particularly transformative in oncology, where early detection and continuous monitoring of cancer are critical for successful treatment outcomes [4]. Unlike conventional methods, which often require invasive tissue biopsies and can be limited by tumor accessibility and heterogeneity, ccfDNA provides a holistic view of the tumor genome.…”
Section: The Emergence Of Circulating Cell-free Dna In Molecular Diag...mentioning
confidence: 99%
“…The rise of ccfDNA has been buoyed by advancements in genomic technologies, enabling the detection and analysis of these DNA fragments with unprecedented precision and sensitivity. Its emergence as a diagnostic tool is particularly transformative in oncology, where early detection and continuous monitoring of cancer are critical for successful treatment outcomes [4]. Unlike conventional methods, which often require invasive tissue biopsies and can be limited by tumor accessibility and heterogeneity, ccfDNA provides a holistic view of the tumor genome.…”
Section: The Emergence Of Circulating Cell-free Dna In Molecular Diag...mentioning
confidence: 99%
“…cfDNA fragments bear unique genetic and epigenetic patterns characteristic to the tumor they originate [222,223]. Understanding of their physical properties and circulation dynamics can facilitate cfDNA optimization and refinement to harness effective theranostic uses [224,225]. Furthermore, kinetic evaluation and molecular profiling through BEAMing (beads, emulsions, amplification, and magnetics), next-generation sequencing (NGS), and digital droplet PCR (ddPCR) are potential non-invasive cancer management modalities.…”
Section: Theranostic Insights In Tumor-tme-bioenergtics Interfacementioning
confidence: 99%
“…The applicability of cfDNA in the prediction of prognosis is another avenue that has been extensively studied in solid tumors with excellent correlation to tissue samples. Many studies have reported that baseline cfDNA concentrations prove to be valuable in the prediction of prognosis in solid tumors, especially renal, breast, genitourinary, and brain tumors ( De Mattos et al, 2011 ; Telekes and Horváth, 2022 ). The recent World Health Organization (WHO) classification update underscores the presence of recurrent mutations in several hematological malignancies ( Alaggio et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%